Association of anti-TNF-α treatment with gut microbiota of patients with ankylosing spondylitis. Issue 7 (12th June 2022) - Dai, Qinghong; Xia, Xuyang; He, Chenjia; Huang, Yupeng; Chen, Yidan; Wu, Yang; Chen, Yuehong; Hou, Qianqian; Shu, Yang; Zhang, Wei; Xu, Heng; Yin, Geng; et al.
Abstract : Objective: Gut dysbiosis contributes to multiple autoimmune diseases, including ankylosing spondylitis, which is commonly treated with tumor necrosis factor (TNF)-α inhibitors (TNFis). Because host TNF-α levels are considered to interact with gut microbiota, we aimed to systematically investigate the microbiota profile of ankylosing spondylitis patients with anti-TNF-α-based treatment and identify potential key bacteria. Methods: Fecal samples were collected from 11 healthy controls and 24 ankylosing spondylitis patients before/after anti-TNF-α treatment, the microbiota profiles of which were evaluated by 16S ribosomal DNA amplicon sequencing and subsequent bioinformatic analysis. Results: Significantly different microbial compositions were observed in samples from ankylosing spondylitis patients compared with healthy controls, characterized by a lower abundance of short-chain fatty acid (SCFA)-producing bacteria. All patients exhibited a positive response after anti-TNF-α treatment, accompanied by a trend of restoration in the microbiota compositions and functional profile of ankylosing spondylitis patients to healthy controls. In particular, the abundance of SCFA-producing bacteria (e.g. Megamonsa and Lachnoclostridium ) was not only significantly lower in ankylosing spondylitis patients than in healthy controls and restored after anti-TNF-α treatment but also negatively correlated with disease severity (e.g. cor = -0.52, P = 8 × 10 −5 for Megamonsa ). In contrast, Bacilli and Haemophilus may contribute to ankylosing spondylitis onset and severity. Conclusions: Microbiota dysbiosis in ankylosing spondylitis patients can be restored after anti-TNF-α treatment, possibly by impacting SCFA-producing bacteria.